2005
DOI: 10.1016/j.femsec.2004.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potential stress responses in ancient Siberian permafrost psychroactive bacteria

Abstract: Past studies of cold-acclimated bacteria have focused primarily on organisms not capable of sub-zero growth. Siberian permafrost isolates Exiguobacterium sp. 255-15 and Psychrobacter sp. 273-4, which grow at subzero temperatures, were used to study cold-acclimated physiology. Changes in membrane composition and exopolysaccharides were defined as a function of growth at 24, 4 and -2.5 degrees C in the presence and absence of 5% NaCl. As expected, there was a decrease in fatty acid saturation and chain length at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 48 publications
5
68
1
Order By: Relevance
“…Increases in both the production of extracellular polymeric substances (acting as cryoprotectants) and in bacterial abundance under similar subzero temperature conditions have been observed in brine channels from sea ice and frost flowers (Krembs et al, 2002;Collins et al, 2008;Meiners et al, 2008;Bowman and Deming 2010;Krembs et al, 2011). This hypothesis is further supported by recent evidence that permafrost isolates have thermohaline-dependent responses for both polysaccharide and fatty acid composition (Ponder et al, 2005) as well as for gene expression patterns (Mykytczuk et al, 2013). Alternatively, the activity of hypo-psychrophilic bacteria may represent a shift in competition for resources, where opportunistic psychrophiles that are adept at garnering nearly all the organic carbon at near freezing temperatures are inactive below À 6 1C.…”
Section: Discussionsupporting
confidence: 57%
“…Increases in both the production of extracellular polymeric substances (acting as cryoprotectants) and in bacterial abundance under similar subzero temperature conditions have been observed in brine channels from sea ice and frost flowers (Krembs et al, 2002;Collins et al, 2008;Meiners et al, 2008;Bowman and Deming 2010;Krembs et al, 2011). This hypothesis is further supported by recent evidence that permafrost isolates have thermohaline-dependent responses for both polysaccharide and fatty acid composition (Ponder et al, 2005) as well as for gene expression patterns (Mykytczuk et al, 2013). Alternatively, the activity of hypo-psychrophilic bacteria may represent a shift in competition for resources, where opportunistic psychrophiles that are adept at garnering nearly all the organic carbon at near freezing temperatures are inactive below À 6 1C.…”
Section: Discussionsupporting
confidence: 57%
“…Our results suggested the existence of one so far unknown lowtemperature-adapted nitrite oxidizer. The adaptation is obviously realized by increasing the percentage of 16:1 cis 9 with decreasing temperature (Table 1), which is a strategy already described for ammonia oxidizing bacteria (Jones and Prahl, 1985) and bacterial isolates from permafrost soils (Ponder et al, 2005). Further enrichment cultures 6679, 6680 and 6681 incubated at 41C, 101C or 171C resulted in this typical pattern for Betaproteobacteria with 16:0 and 16:1 cis 9 as dominating compounds, too (not shown).…”
Section: Chemotaxonomic Analysismentioning
confidence: 65%
“…can grow with additional NaCl in their medium (Romanenko et al, 2004;Shivaji et al, 2005;Rodrigues et al, 2006;Crapart et al, 2007). This evidence suggests that these genera are adapted to salinity, which would explain the strong correlation of the abundance of these genera to moderate to high salinity habitats, that is, Antarctic marine sediments, the Puerto Rican mangroves and the Siberian permafrost, the latter due to its limited but salty liquid phase (low water activity) (Ponder et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Studies with Psychrobacter and Exiguobacterium spp. isolated from the Siberian permafrost have shown that these genera can tolerate increased osmolarity and show associated changes in membrane composition, cell morphology and size (Ponder et al, 2005). Furthermore, all isolates from Exiguobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation